FAKTOR-FAKTOR YANG MEMENGARUHI PENDUDUK LANJUT USIA MASIH BEKERJA - Ni Kadek, Andini; Desak PUtu, Nilakusmawati Eka; Made, Susilawati (PIRAMIDA; Vol 9, No. 1 Juli 2013, 2013)
This research aims to determine the factors that affect the elderly are still working. This data was obtained through questionnaire distribution to the elderly. Elderly in this study is elderly aged 60-74 years old and retired. Sampling technique that are used on this survey are purposive sampling combined with accidental sampling. The variables of this study are: level of education (X1), status in the household (X2), marital status (X3), length of illness in the week (X4), dependency of family member (X5),  annuity  and labour status of elderly (X6). The  technique og data analysis that are used is the log-linear analysis. The study found that elderly labour status associated with presence/absence of dependency of family mamber  and the presence/absence of old-age benefits, labourt status associated with the status of the elderly in the household and in a week long illness, labour status associated with marital status and presence/ absence of annuity, as well as status in the household interact with marital status and length of illness within a week. The conclusion of this research showed that the factors that affect of the elderly are still working is the status in the household, marital status, length of illness in the week, presence/absence of family member dependency, presence/ absence of annuity, while the level of education also influenced indirectly.
Keywords: Elderly; Working elderly; Working Elderly Factors; Log-Linear Analysis